PESANTREN DAN GLOBALISASI: PRIBUMISASI PERADABAN ISLAM DI ASIA TENGGARA - Asroni (Al'Adalah, 2014)
Pesantren have the role and a significant contribution in the development of Islamic civilization in southeast asia .The role of Pesantren seem especially in an effort to form the community of literate (literacy) and cultural literacy. Pesantren also known as the base of resistance against the colonial government. In malaysia, a network many scholars who dominated the early history of Islamic movement more played by the Pesantren alumnus and some alumnus of the middle east who never learn in a Pesantren. In southern thailand, Ponoh has provided a significant contribution to the development of islamic studies in Southeast Asia. Similarly in the philippines, a discussion on Islam and Pesantren is still always coloring the history of Islamic education. One important contribution of Pesantren are developing of Java and the Malay language. To return back Pesantren as the center of Islamic civilization in Southeast Asia, Pesantren necessary to update and modernization in every aspect without abandoning distinctness. Should also think again the importance of building a modern Pesantren in Southeast Asia. The Southeast Asian Pesantren network is expected to rebuild the format and the role of Pesantren, not only deliver Islamic Scholars but also the Government. Pesantren must also unlock dialogue with other cultural in Southeast Asia. Thus, Pesantren will constantly stand ready to carry on negotiations with the spirit of scientific and cultures everywhere, so the Pesantren contribute very significant for the civilization of Islam in Southeast Asia.